Sustainable beef labeling in Latin America and the Caribbean: Initiatives, developments, and bottlenecks - Moreno Lerma, Leonardo; Díaz Baca, Manuel F.; Burkart, Stefan (Frontiers Media, 2023)
Scientific research is increasingly conclusive regarding the responsibility of food production in environmental issues, a situation that contrasts with greater consumer awareness. In this context, sustainability labels for meat have emerged, which offer a guarantee that production is based on principles of animal welfare, and carbon neutrality, among others. Since research on this subject is scarce, the objective of this article is to identify and analyze the initiatives and development of this type of labeling in Latin America and the Caribbean. For this purpose, a qualitative-descriptive study is carried out based on primary and secondary sources. The results show different types of progress in the main producing countries, with Uruguay and Brazil standing out as success stories. At the same time, difficulties are highlighted in the different stages of the production chain, such as low demand, or traceability. It is concluded that, despite the challenges, the transition to sustainable cattle farming is inevitable. However, this process will not happen spontaneously, but must be coordinated up with other types of strategies and the actions of various actors including governments, policymakers, and NGOs.